The persistent challenge of alternatives to peat in container-based horticulture: a historical review of the field of growing media - Aurdal, Siv Mari (Frontiers in Horticulture, 2025)
This paper is a historical review of scientific progress on horticultural growing media, with particular attention to the role of peat and the recurring search for sustainable alternatives. It is well established that peat became the cornerstone of horticultural growing media because it offered a unique combination of nutrient control, pH buffering, water retention, absence of harmful microorganisms, and structural stability. Equally evident are the environmental concerns and sustainability goals that have driven the search for alternative materials since the 1980s. This historical review traces the evolution of growing media from the early 20th century to the mid-2020s, focusing on how peat came to dominate and why its substitution has proven so difficult. Drawing on a wide range of literature, including peer-reviewed experimental studies, historical sources, symposia proceedings, institutional reports, and synthesis articles, the historical development of growing media science and practice across each decade is outlined. Attention is given to various composts, coir, wood fiber, bark, and biochar and challenges with these materials related to product standardization for end-user reliability. While many alternatives show potential, particularly as partial components or as stand-alone media under certain conditions, no single material currently offers a fully viable replacement for peat. Instead, the most promising direction appears to be peat-reduced mixtures optimized for both functionality and sustainability. By understanding how growing media science has evolved and where it has struggled, this paper identifies lessons critical to navigating the ongoing transition toward more sustainable and functional systems.